Effect of Water on Some Mechanical Properties for Sawdust and Chopped Reeds /UPE composites - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
In this study, composite materials were prepared using unsaturated polyester resin as binder with two types of fillers (sawdust and chopped reeds). The molding method is used to prepare sheets of UPE / sawdust composite and UPE / chopped reeds composite. The mechanical properties were studied including flexural strength and Young's modulus for the samples at normal conditions (N.C). The Commercial wood, UPE and its composite samples were immersed in water for about 30 days to find the weight gain (Mt%) of water for the samples, also to find the effect of water on their flexural strength and Young's modulus. The results showed that the samples of UPE / chopped reeds composite gained highest values of flexural strength (24.5 MPa) and Young's modulus (5.1 GPa) as compared with other composites at (N.C). The results showed that the wet samples of sawdust composite have lowest values of weight gain (Mt %) of water (0.043%) as compared with other composites after immersion. Also it’s showed a slight decrease in values of Young's modulus for all the samples after immersion as compared with the samples at (N.C). Finally it’s showed a slight decrease in values of flexural strength for all the samples except for the composite material formed from UPE / chopped reeds which showed an increase in the value of flexural strength after immersion, where the wet samples of UPE / chopped reeds composite gained (29 MPa) as compared with the samples at (N.C).